ICT adoption and public value creation in performance audits: Evidence from Indonesia’s migrant worker protection - Yulianto, Eko; Wijaya, Satria Yudhia; Muqaibal, Abdullah Aqeel (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
This study explores the role of Information and Communication Technology (ICT) in enhancing public value through performance audits, focusing on the protection of Indonesian migrant workers. Using a qualitative case study method, it analyzes BPK audits and considers both internal and external factors influencing ICT-based audit practices. Data were collected through interviews with auditors, analysis of audit reports, and a review of relevant regulations. The findings highlight internal factors—such as the use of cloud storage, digital communication tools, and electronic forms—that significantly enhance audit efficiency and effectiveness. These tools simplify data collection, facilitate communication, and expedite reporting, resulting in more structured, timely audits. At the same time, external challenges, including fragmented data systems, a lack of interoperability among government agencies, and uneven ICT adoption, created inefficiencies and additional workloads for auditors. These constraints limited the capacity of audits to fully deliver public value. This study concludes that ICT strengthens audit processes, but its full potential can be realized only if audited entities adopt integrated, interoperable digital systems. In practice, enhancing cross-agency collaboration and strengthening digital infrastructure are essential to maximizing the public value of ICT-enabled performance audits.